The Impact of Streamer Marketing on Consumer Purchasing Behavior in the Live-Stream Economy - Xu Zhanlin (SHS Web of Conferences)
Face-to-face video connection via online live stream decreases knowledge asymmetry between buyers and sellers and has emerged as a new economic model in the wake of the COVID-19 epidemic. Based on this new economic model, this study focuses on the impact of streamer marketing methods on customer purchasing behavior. Through questionnaire survey research, it is found that the current live stream economy has become an economic model with high participation. Consumers are generally less affected by streamer marketing strategies, and their buying behavior is generally more rational. Quality marketing in streamer marketing methods will significantly enhance consumers’ purchasing behavior. After impulse buying, consumers are more rational and will properly dispose of unnecessary goods. Finally, results are discussed based on the research.